Inkluzywna i przyjazna instytucja kultury - Biblioteka Publiczna Miasta i Gminy w Międzyrzeczu = An Inclusive and Welcoming Cultural Institution - The Public Library of the Town and Municipality of Międzyrzecz - Pawłowska, Krystyna (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
In 2024, ten years will have passed since the completion of the project titled "Renovation and Reconstruction of the Public Library in Międzyrzecz." This article presents the Międzyrzecz Library as a welcoming and universally accessible cultural institution, focusing on four key aspects of its operations: the library?s place and role in the local community, the renovation and modernization of its spaces, changes in its cultural and educational offers, and the long-term effects of these transformations ? remodeling reminiscences. The author also addresses the conveniences introduced for both internal users (staff) and external users (actual and potential library service recipients).
Keywords: biblioteka publiczna; Międzyrzecz; modernizacja; estetyka; funkcjonalność; partnerstwo; public library; modernization; aestetics; functionality; partnership